Reassortant swine influenza viruses isolated in Japan contain genes from pandemic A(H1N1) 2009. (June 2014) - Kanehira, Katsushi; Takemae, Nobuhiro; Uchida, Yuko; Hikono, Hirokazu; Saito, Takehiko
ABSTRACT In 2013, three reassortant swine influenza viruses (SIVs)—two H1N2 and one H3N2—were isolated from symptomatic pigs in Japan; each contained genes from the pandemic A(H1N1) 2009 virus and endemic SIVs. Phylogenetic analysis revealed that the two H1N2 viruses, A/swine/Gunma/1/2013 and A/swine/Ibaraki/1/2013, were reassortants that contain genes from the following three distinct lineages: (i) H1 and nucleoprotein (NP) genes derived from a classical swine H1 HA lineage uniquely circulating among Japanese SIVs; (ii) neuraminidase (NA) genes from human‐like H1N2 swine viruses; and (iii) other genes from pandemic A(H1N1) 2009 viruses. The H3N2 virus, A/swine/Miyazaki/2/2013, comprised genes from two sources: (i) hemagglutinin (HA) and NA genes derived from human and human‐like H3N2 swine viruses and (ii) other genes from pandemic A(H1N1) 2009 viruses. Phylogenetic analysis also indicated that each of the reassortants may have arisen independently in Japanese pigs. A/swine/Miyazaki/2/2013 were found to have strong antigenic reactivities with antisera generated for some seasonal human‐lineage viruses isolated during or before 2003, whereas A/swine/Miyazaki/2/2013 reactivities with antisera against viruses isolated after 2004 were clearly weaker. In addition, antisera against some strains of seasonal human‐lineage H1 viruses did not react with either A/swine/Gunma/1/2013 or A/swine/Ibaraki/1/2013. These findings indicate that emergence and spread of these reassortant SIVs is a potential public health risk.